Outcomes following burn injury in intensive care patients with major psychiatric disorders. Issue 4 (June 2023) - Obed, Doha; Schroeter, Andreas; Gruber, Lisa; Salim, Mustafa; Krezdorn, Nicco; Vogt, Peter M.
Abstract: Aims: Patients with psychiatric comorbidity have been shown to experience high rates of burn injury. Burn epidemiology, etiology, and outcomes have been sparsely documented for patients with major psychiatric disorders. The aim of this study was to analyze the epidemiologic characteristics and outcomes in intensive care burn patients with pre-existing and acute major psychiatric disorders . Methods: A retrospective study was performed including intensive care burn patients admitted between March 2007 and December 2020. Demographic, clinical and epidemiological data were collected and analyzed. Major psychiatric co-morbidities were collected according to ICD-9 and ICD-10 classifications. Patients were stratified according to F-diagnoses. Results: A total of 1325 patients were included. 16.6 % of all patients had one or more major psychiatric disorders- 9.3 % with anxiety, dissociative, stress-related, somatoform and other nonpsychotic mental disorders, 9.2 % with mood (affective) disorders, 3.5 % with schizophrenia and other non-mood psychotic disorders, and 1.8 % with disorders of adult personality and behavior. Patients with major psychiatric disorders presented with significantly higher burn severity, reflected by higher abbreviated burn severity index (ABSI) scores (5.9 vs. 5.3, p  < 0.001) and larger total body surface area (TBSA) affected (15.9 vs. 12.5 %, p  = 0.002). Burned TBSA ≥ 30 and inhalation injuries were observed more frequently in patients with MDP, however without statistical significance. They also experienced prolonged hospital length-of-stay (LOS) (25.5 vs. 16.3 days, p  < 0.001), p rolonged intensive care unit LOS (14.8 vs. 7.7 days, p  < 0.001), underwent surgical interventions (3.5 vs. 2.3, p  < 0.001) and mechanical ventilation more frequently (34.1 % vs. 16.5 %, p  = 0.43) and had significantly longer ventilation durations (73.5 vs. 31.2 h, p  = 0.002). Mortality rates were lower compared to patients without major psychiatric disorders (5.9 vs. 8.1, p  < 0.001). Conclusions: The prevalence of major psychiatric disorders in burn patients is considerably high. Patients with psychiatric comorbidities were found to have greater burn severity, prolonged total hospital and ICU LOS, underwent surgical interventions and mechanical ventilation more frequently and had prolonged ventilation duration. Our results highlight the importance of identifying burn patients with major psychiatric disorders who may necessitate additional resources and require extensive inpatient psychiatric care and counseling. Highlights: 16.6 % of the ICU burn patients had a major psychiatric comorbidity. Patients with major psychiatric disorders required more surgical interventions. They had greater burn severity and longer hospital stays and ventilation durations. This effect was pronounced in patients with schizophrenic/psychotic conditions. Mortality rates were higher in patients without major psychiatric disorders.